Peri‐Aortic Fluid: A Critical Finding in Acute Aortic Syndrome. Issue 8 (12th May 2014) - Barake, Walid; Oqab, Zardasht; Najib, Syed Samir; Hamilton, Andrew; Johri, Amer M.
Mini‐Abstract A case of acute aortic syndrome (AAS) in a 70‐year‐old patient is described. Peri‐aortic fluid on echocardiography was a key for early diagnosis and surgical intervention. Peri‐aortic fluid, even in the absence of dissection on imaging, is a critical finding in AAS which has been underappreciated in the literature.